A crystalline diazadiborinine radical cation and its boron-centered radical reactivity - Wang, Baolin (2020)
One‐electron oxidation of 1,4,2,5‐diazadiborinine 1 has been studied. While the reaction of 1 a bearing phenyl groups on the B atoms with AgAl{OC(CF3)3}4 afforded a complex mixture, the same oxidation reaction with 1 b featuring bulky mesityl substituents on the B atoms rendered the corresponding cation radical 2 b as an isolable species. X‐ray diffraction analysis, EPR spectroscopy, and DFT calculations of 2 b revealed the delocalization of the unpaired electron over the entire π‐system of 2 b, as well as a large spin density (0.76 in total) on the two equivalent boron atoms. The chemical trapping reaction of 2 b with p‐benzoquinone and triphenyltin hydride afforded the dicationic species 3 containing two newly formed B−O bonds and the monocationic product 2b‐H containing a B−H bond, respectively, thus confirming the boron‐centered radical reactivity of 2 b.